Helix-Sense-Selective Polymerization of Achiral Phenylacetylenes and Unique Properties of the Resulting Cis-cisoidal Polymers. (2nd January 2017) - Liu, Lijia; Zang, Yu; Jia, Hongge; Aoki, Toshiki; Kaneko, Takashi; Hadano, Shingo; Teraguchi, Masahiro; Miyata, Mari; Zhang, Geng; Namikoshi, Takeshi
ABSTRACT: One of the authors discovered helix-sense-selective polymerization (HSSP) of an achiral substituted phenylacetylene which has two hydroxymethyl groups and a relatively hydrophobic substituent by using a chiral catalytic system in 2003. The one-handed helicity is stable and static in nonpolar solvents because it is maintained by intramolecular hydrogen bonds. Since the resulting polymer has extremely tight helicity in its main chain, it shows many interesting and unusual properties including highly selective photocyclic aromatization (SCAT). In this review, the discovery and development of the HSSP and SCAT reactions, and the properties and application of the resulting polymers prepared by HSSP and the resulting supramolecular polymers prepared by SCAT will be examined.